Socialization of Maintaining Environmental Cleanliness in the Face of the Covid-19 Pandemic - I Wayan Aditya Tariana (Syntax Corporation Indonesia, 2023)
The beginning of 2020 was an extraordinary event for the whole world. This is because almost all parts of the world are hit by the Covid-19 outbreak which causes unrest and has a big impact on every field. The COVID-19 pandemic makes people have to maintain their health by washing their hands, maintaining distance, not crowding, and maintaining cleanliness (Abidin, et al., 2021). Buhungo (2012) explained that environmental cleanliness is a condition where the environment is free from various kinds of dirt and disease that can cause losses to the community, both from activities and the environment. The condition of the COVID-19 pandemic forces every community to maintain cleanliness, both their personal hygiene and also the cleanliness of their environment. To provide assistance to the community, especially in the village of Kedisan Kintamani, the Faculty of Economics and BEM-FEB Universitas Pendidikan Nasional (UNDIKNAS) Denpasar collaborate in holding community social activities which are also under the auangan of LP2M and the Dean of FEB UNDIKNAS. The community social activities were held with the theme